Multisymptom long COVID in a patient with psoriatic arthritis: a case report - Menkus, Olena; Grishyna, Olena (Annals of Mechnikov’s Institute, 2025)
A 62-year-old female patient diagnosed with psoriasis involving the skin and nails, psoriatic arthritis, and enthesitis; arterial hypertension, stage II, grade 2, moderate risk, NYHA II. She received secukinumab 150 mg subcutaneously once every 4 weeks for the treatment of psoriasis. Blood pressure (BP) was controlled with carvedilol 12.5 mg/day. She was vaccinated against COVID-19 (3 ​​doses in 2021) and fell ill with COVID-19 in September 2022. She was treated as an outpatient. No lung damage was detected on X-ray. The deterioration of the condition began 2 months after the onset of COVID-19 (hair loss, increased shortness of breath, progression of weakness). After 3 months - increased weight, unstable blood pressure (initially increased, then decreased to normal values), inappropriate sinus tachycardia. The dose of carvedilol was reduced to 3.125 mg/day. She could not take ivabradine because of the proarrhythmogenic effect. The patient also developed skin itching and recurrent herpetiform rashes on the lips. The patient assessed them as Herpes labialis. Over the course of six months, these rashes recurred 4-5 times, tachycardia and a tendency to decrease blood pressure persisted. Ten months after acute COVID-19, unbearable skin itching, bullous rashes with a flaccid membrane, serous contents, positive Nikolsky’s symptom throughout the body, eosinophilia appeared. The dermatologist diagnosed pemphigus and prescribed methylprednisolone 32 mg / day. In June 2024 (1 year and 9 months after the onset of the disease), she began to notice interruptions in the heart, shortness of breath, intolerance to minor stress, both physical and emotional, due to the appearance of attacks of palpitations. With daytime monitoring of the heart rate - against the background of sinus rhythm with an average daily heart rate of 81 beats / min. rare (at least 14) supraventricular (atrial polytopic) extrasystole are determined, in particular as part of a triplet; frequent (more than 5.0 thousand, up to 522 per hour) polymorphic ventricular parasystole. Takes carvedilol 3.125 mg / day, etacizin 100 mg / day. Also in October 2024, skin itching and a single blister on the lip appeared again (she used betimethasone ointment), parasystole persists.